Influence of Infill Density on the Mechanical Properties of FFF 3D-Printed PLA and PLA+CF Materials - Horvat, Gregor; Kek, Izar Gaj; Knap, Boštjan; Komočar, Marina; Okorn, Maja; Hozdić, Elvis (Advanced Technologies and Materials, 2026)
Fused Filament Fabrication (FFF) has become one of the most widely adopted additive manufacturing technologies for polymer-based components, particularly for polylactic acid (PLA) and carbon fiber–reinforced PLA (PLA+CF) materials. Among processing and structural parameters, infill density has been identified as a critical factor governing mechanical performance and environmental durability of printed parts. However, experimental findings reported in the literature remain fragmented and are often influenced by interacting process variables, limiting the direct transferability of results to engineering design. This study presents a structured comparative synthesis and analytical review of previously published experimental datasets addressing the influence of infill density on tensile strength, elastic modulus, and failure behavior of FFF-printed PLA and PLA+CF materials. The analysis integrates results from three peer-reviewed studies, including data obtained under dry conditions and after controlled exposure to industrial lubricants. Density-dependent trends are systematically evaluated to identify consistent mechanical responses across different material systems and service environments. The results demonstrate that increasing infill density generally improves tensile strength and stiffness due to reduced internal porosity and enhanced interlayer bonding. However, maximum load-bearing capacity does not always increase monotonically with densification, indicating the presence of optimal intermediate infill ranges. Environmental exposure is shown to cause density-dependent mechanical degradation, with higher infill densities providing improved resistance to lubricant penetration and stiffness loss. PLA+CF exhibits higher stiffness compared to neat PLA, while also showing increased sensitivity to brittle failure mechanisms. The presented synthesis provides design-oriented insights into the role of infill density as a primary structural control parameter, supporting performance optimization of FFF-printed polymer components without modifications to material composition or processing hardware.